Pharmacokinetics and Dose Optimization Strategies of Para-Aminosalicylic Acid in Children with Rifampicin-Resistant Tuberculosis - van der Laan, Louvina E; Garcia-Prats, Anthony J; Schaaf, H Simon; Chirehwa, Maxwell; Winckler, Jana L; Mao, Jun; Draper, Heather R; Wiesner, Lubbe; Norman, Jennifer; McIlleron, Helen; Donald, Peter R; Hesseling, Anneke C; et al. (Antimicrobial agents and chemotherapy, 2022)
Treatment options for children with Rifampicin-resistant tuberculosis (RR-TB) remain limited, and para-aminosalicylic acid (PAS) is still a relevant component of treatment regimens. Prevention of resistance to companion drugs by PAS is dose related, and at higher concentrations, PAS may exhibit significant bactericidal activity in addition to its bacteriostatic properties. The optimal dosing of PAS in children is uncertain, specifically for delayed-release granule preparations, which are the most used. A population pharmacokinetic model was developed describing PAS pharmacokinetics in children receiving routine RR-TB treatment. Model-based simulations evaluated current World Health Organization (WHO) weight-band doses against the adult pharmacokinetic target of 50 to 100 mg/liter for peak concentrations. Of 27 children included, the median (range) age and weight were 3.87 (0.58 to 13.7) years and 13.3 (7.15 to 30.5) kg, respectively; 4 (14.8%) were HIV positive. PAS followed one-compartment kinetics with first-order elimination and transit compartment absorption. The typical clearance in a 13-kg child was 9.79 liters/h. Increased PAS clearance was observed in both pharmacokinetic profiles from the only patient receiving efavirenz. No effect of renal function, sex, ethnicity, nutritional status, HIV status, antiretrovirals (lamivudine, abacavir, and lopinavir-ritonavir), or RR-TB drugs was detected. In simulations, target concentrations were achieved only using the higher WHO dose range of 300 mg/kg once daily. A transit compartment adequately describes absorption for the slow-release PAS formulation. Children should be dosed at the higher range of current WHO-recommended PAS doses and in a once-daily dose to optimize treatment.